DYNAMICS OF NOMINAL EXCHANGE RATE WITH PRICE LEVELS: WHAT HAPPENS IN INTERNATIONAL MARKETS? - Taqqadus Bashir; Aaqiba Javed; Ali Raza; Muhammad Arif Ali; Anam Ameer Ali; Marria Hassan (European Scientific Journal, ESJ, 2013)
Since inception exchange rate determination in Pakistan has been studied extensively but under various approaches. Current study explores empirically the relationship of the domestic price level & foreign price level with nominal exchange rate in Pakistan, using a daily data set for 13 years (July 2000- June 2013) as provided by State Bank of Pakistan. Variables are analyzed for stochastic properties and existence of unit root, for this purpose ADF is used. Along with regression analysis the co-integration is tested to detect long term co-movement between variables. It has been found that domestic price level has positive relationship with nominal exchange rate, whereas, foreign price level has a negative relationship with nominal exchange rate in the long run.